Regiospecific synthesis of some novel N-nucleosides of 4-amino-5-substituted-1,2,4-triazole-3-thiones and their in-vitro antimicrobial activity - Nadeem, Humaira; Ashraf, Zaman (European Journal of Chemistry, 2012)
4-Amino-5-substituted-1,2,4-triazole-3-thiones were prepared by following two different reaction routes and comparing the effectiveness of using different reaction conditions. The coupling of aminotriazoles with acetylated α-bromo-D-glucose furnished protected N-nucleosides regiospecifically. The reagents used gave only one regioisomer N-glycosides not the other S-nucleosides. The protected nucleosides upon deacetylation using methanolic ammonia afforded deprotected products. The chemical structures of synthesized compounds were confirmed by FT-IR, 1H NMR, 13C NMR, mass spectroscopic and elemental analysis data. All of the synthesized compounds were tested against ten different gram positive and gram negative bacterial strains which exhibited moderate to good antibacterial activity. The deprotected nucleosides portrayed high antibacterial activity than 4-amino-5-substituted-1,2,4-triazole-3-thiones and protected nucleosides against selected bacteria.